2021
DOI: 10.3389/fimmu.2021.726215
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of 313 Czech Patients With IgA Nephropathy After Renal Transplantation

Abstract: The recurrence of IgA nephropathy (IgAN) after kidney transplantation occurs in 20–35% of patients. The main aim of this study is to evaluate risk factors affecting the course of IgAN after renal biopsy of native kidney and kidney transplant. We evaluated clinical parameters and histological findings at the time of biopsy of native kidney and after kidney transplantation in 313 patients with IgAN with a follow-up of up to 36 years. Using hierarchical clustering method, patients with graft failure (n=50) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…found that the living donor was not related to the recurrent IgAN [24]. Our study showed that living donor transplantation increased the risk of recurrence of IgAN after renal transplantation, especially the living related donor (P < 0.05).…”
Section: Discussionmentioning
confidence: 48%
“…found that the living donor was not related to the recurrent IgAN [24]. Our study showed that living donor transplantation increased the risk of recurrence of IgAN after renal transplantation, especially the living related donor (P < 0.05).…”
Section: Discussionmentioning
confidence: 48%
“…Several risk factors were documented in the literature that are associated with high recurrence rates, including receiving a living donor kidney, HLA matching, a younger age at transplant, and so on . 1,3,19 In 313 patients with IgAN with a follow-up of up to 36 y, Maixnerova et al 20 used the hierarchical clustering method to identify risk factors of recurrence and outcome. Patients with graft failure (n = 50) were divided into 2 groups based on the mean time from kidney transplant to graft failure (11.2 versus 6.1 y).…”
Section: Discussionmentioning
confidence: 99%
“…Reports of recurrent disease in IgAN are variable and time-dependent [25,26 ▪▪ ], with an estimated 13–25% of patients experiencing recurrence by 5 years, and as high as 60% by 15 years. Variability likely depends on whether centers practice protocol surveillance biopsies or not.…”
Section: Iga Nephritis and Iga Vasculitismentioning
confidence: 99%
“…Variability likely depends on whether centers practice protocol surveillance biopsies or not. Median time to recurrence has been reported at 3–4 years [23 ▪▪ ,26 ▪▪ ,27 ▪ ,28 ▪ ,29]. Pediatric patients are at higher risk of recurrence than adults [25,30].…”
Section: Iga Nephritis and Iga Vasculitismentioning
confidence: 99%